2019
DOI: 10.3390/ijms20246183
|View full text |Cite
|
Sign up to set email alerts
|

Protein Misfolding during Pregnancy: New Approaches to Preeclampsia Diagnostics

Abstract: Preeclampsia (PE) is a multisystem heterogeneous complication of pregnancy remaining a leading cause of maternal and perinatal morbidity and mortality over the world. PE has a large spectrum of clinical features and symptoms, which make diagnosis challenging. Despite a long period of studying, PE etiology is still unclear and there are no reliable rapid tests for early diagnosis of this disease. During the last decade, it was shown that proteins misfolding and aggregation are associated with PE. Several protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 152 publications
(205 reference statements)
0
24
0
1
Order By: Relevance
“…Many proteins, like amyloid beta peptide, transthyretin, alpha-1 antitrypsin, albumin, and ceruloplasmin are misfolded, and the amyloid-like aggregates are found in the placenta, as well as in body fluids. These aggregates appear to induce ER stress, impaired trophoblast invasion, and placental ischemia, which culminates in PE condition [ 169 ].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…Many proteins, like amyloid beta peptide, transthyretin, alpha-1 antitrypsin, albumin, and ceruloplasmin are misfolded, and the amyloid-like aggregates are found in the placenta, as well as in body fluids. These aggregates appear to induce ER stress, impaired trophoblast invasion, and placental ischemia, which culminates in PE condition [ 169 ].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…The most important amyloid-associated diseases include Alzheimer’s and Parkinson’s diseases, type 2 diabetes, and transmissible spongiform encephalopathies (TSEs), or prion diseases, such as Creutzfeldt-Jakob disease [ 6 ]. Recent data indicate that amyloids are also associated with preeclampsia and some forms of cancer, although this is unclear whether amyloids cause these diseases or arise as a consequence of the disease and serve as biomarkers [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, A1AT-OE or A1AT administration increases the migration and invasion of human umbilical vein endothelial cells from women with PE [ 19 ]. Conversely, it has been reported that A1AT expression is high in placentas from patients with PE [ 24 ] and that the urinary A1AT concentration is high in women with PE [ 5 , 25 , 26 ]. Our data suggest that A1AT regulates cell motility via ER stress and HTRA1 expression in trophoblast cells, and that dysregulation may be associated with complications of pregnancy, including PE ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%